1979
DOI: 10.2105/ajph.69.11.1132
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of women and men physicians.

Abstract: Attitudinal data obtained from interviewing random samples of women and men physicians in metropolitan Detroit indicated that women were generally more liberal and egalitarian than men. Older women were more liberal/egalitarian than older men while younger men were closer in attitudes to younger women. Within specialties, women and men physicians frequently held similar attitudinal scores; however, controlling for age, sex accounted for more variation than did specialty. A weighted combination additional 12 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 26 publications
0
7
1
1
Order By: Relevance
“…The response rate of 88% in this study was very satisfactory and somewhat higher than a number of similar surveys among the medical profession (Burgess et al 1978; Heins et al 1979; Wechsler et al 1983; Fortmann et al 1985). The relatively smaller sample and the fact that this survey was conducted in conjunction with another study on the training and career choices of the young doctors may explain partly the high response rate which contributed to the validity of our findings.…”
Section: Discussioncontrasting
confidence: 40%
“…The response rate of 88% in this study was very satisfactory and somewhat higher than a number of similar surveys among the medical profession (Burgess et al 1978; Heins et al 1979; Wechsler et al 1983; Fortmann et al 1985). The relatively smaller sample and the fact that this survey was conducted in conjunction with another study on the training and career choices of the young doctors may explain partly the high response rate which contributed to the validity of our findings.…”
Section: Discussioncontrasting
confidence: 40%
“…This finding accords with those from other studies. Women students and doctors differ from their men colleagues in both attitudes to patients and their communication skills, tending to hold more positive attitudes to giving patients information and showing more empathic behaviour in consultations (Heins et al 1979; Bean & Kidder 1982; Wasserman et al 1984; Weisman & Teitelbaum 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that women possess greater sensitivity to social issues than do men, which will, over time, affect the medical profession's position on matters such as national health insurance (Heins et al, 1979;Relman, 1980), or at least its willingness to experiment with different economic arrangements for medical practice (Relman, 1989). The most widely shared prediction about the effects of increased numbers of women in medicine has been that women physicians will give the profession an increased capacity for demonstrating caring attitudes toward patients (e.g., Elliott, 1981;Zeno, 1982), which may be "more valuable in healing than all the medicine in the textbooks" (Keeler, 1980:8).…”
Section: Gender and The Practice Of Medicinementioning
confidence: 99%